2006
DOI: 10.1007/s10658-006-9000-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Structure of Mycosphaerella graminicola Populations from Iran, Argentina and Australia

Abstract: Restriction fragment length polymorphism (RFLP) markers were used to assess the genetic structure of populations of Mycosphaerella graminicola collected from wheat fields. A total of 585 isolates representing 10 field populations were sampled from Iran, Argentina and Australia. The genetic structure of M. graminicola populations from Iran and Argentina is described for the first time. Results were compared to previously investigated populations from Israel, Uruguay and Australia. Populations from Iran exhibite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
1
5

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 21 publications
3
13
1
5
Order By: Relevance
“…Necochea 50 and 52 Tres Arroyos 202,226,228,229,232,236,237,238,249,255,260 Our analysis showed that there was higher genotype diversity in the population from wheat subregion IV than in that from subregion II South. Our results are in agreement with those of Jürgens et al (2006) and Cordo et al (2006), who found different rates of genotype diversity when comparing populations in Argentina using RFLP. Jürgens et al (2006) studied five populations from three different locations: Los Hornos (ARG1 and ARG5), Balcarce (ARG2) and Barrow (ARG3 and ARG4), and found that 65% of all isolates were unique genotypes.…”
Section: Isolates Originsupporting
confidence: 93%
See 3 more Smart Citations
“…Necochea 50 and 52 Tres Arroyos 202,226,228,229,232,236,237,238,249,255,260 Our analysis showed that there was higher genotype diversity in the population from wheat subregion IV than in that from subregion II South. Our results are in agreement with those of Jürgens et al (2006) and Cordo et al (2006), who found different rates of genotype diversity when comparing populations in Argentina using RFLP. Jürgens et al (2006) studied five populations from three different locations: Los Hornos (ARG1 and ARG5), Balcarce (ARG2) and Barrow (ARG3 and ARG4), and found that 65% of all isolates were unique genotypes.…”
Section: Isolates Originsupporting
confidence: 93%
“…Our results are in agreement with those of Jürgens et al (2006) and Cordo et al (2006), who found different rates of genotype diversity when comparing populations in Argentina using RFLP. Jürgens et al (2006) studied five populations from three different locations: Los Hornos (ARG1 and ARG5), Balcarce (ARG2) and Barrow (ARG3 and ARG4), and found that 65% of all isolates were unique genotypes. Likewise, Cordo et al (2006) studied the populations from Balcarce (subregion IV) and Los Hornos (subregion II South), and found 39 genotypes among 62 isolates of the pathogen in Balcarce and 35 unique genotypes among a total of 58 isolates in Los Hornos.…”
Section: Isolates Originsupporting
confidence: 93%
See 2 more Smart Citations
“…Ces processus fournissent de nouvelles combinaisons de virulence à l'intérieur de la population du pathogène. Buxton (1960) et Osbumet al, (1987 (Boegeret al, 1993;Chen et al, 1994;McDonald et al, 1996;Cristina et al, 1997;Zhan et al, 2003;Jurgens et al, 2006). Cette dernière est mise en évidence par utilisation des techniques de marquage moléculaire (PCR, RAPD, AFLP, FRLP, SSR…...).…”
Section: II Iii Iv V Viunclassified